NORM in Markazia Degasing Station within North Rumaila Oilfield- Southern Iraq - Ali, Kamal K.; Husain, Husain A.; Shafik, Shafik Sh. (Iraqi Journal of Science, 2021)
Concentration of natural occurring radioactive material (NORM) in Markazia Degasing Station in North Rumaila oilfield (NDS) was measured in this study. Then, radiological assessment due to existing of NORM in different samples including soil, sludge, scale, oil, and water collected from different stages of oil and gas production NDS was done. Radioactivity concentration of Ra-226, Th-232 and K-40 were measured using gamma spectrometry system based on HPGe detector with efficiency of 30%. The results show that some locations within NDS are contaminated with NORM. The activity in Bq/kg of Ra-226, Th-232 and K-40 range between 15.19 in oil to 68.73 in sludge, 8.5 in oil to 23.45 in sludge and 80.23 in oil to 319.73 in saline water samples respectively. The places to be more contaminated among the other places within the processing stages of oil and gas production within NDS are dehydrator and desaltor stages. These locations have to be monitored and remediated periodically.